THE IMPORTANCE OF KNOWLEDGE AND UNDERSTANDING OF LOCAL STYLES OF FOLK MUSIC IN THE FIELD OF EDUCATION - Fozilov Kahramon Madaminovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article gives leading importance to the use of national musical heritage. Currently, music is distinguished from other aesthetic subjects by its relevance and importance in the education and upbringing of students. Music lesson is an integral part of the general education system, it helps to develop emotional and creative feelings in children and enrich their artistic impressions. This is an important way to form a child's personality.